Legal Instruments Used to Hedge the Risk of Late Payments in Business Activity in Poland - Anna OLKIEWICZ (Communications of International Proceedings, 2024)
Data on payment terms in business-to-business transactions show that the average payment term in Europe is more than 50 days. This means that you have to credit the contractor and risk that you will not be paid at all. Entrepreneurs suffer losses due to late payments, and some companies are forced to restructure their businesses or declare bankruptcy because of this. The article discusses a significant problem concerning the impact of delays in payments on the business activity of entrepreneurs and the available instruments of protection against delays in payments from the contractor. This is an important issue for the economy, as late payments cause payment gridlocks, in which many entrepreneurs may participate. Literature, practice and law have developed many instruments to prevent delays. Unfortunately, it turns out that despite many tools, we are still dealing with delayed payments. The aim of the article is to indicate how to deepen the knowledge about the tools available to entrepreneurs to protect themselves against delays in payments from the contractor and the instruments that can help in faster recovery of already delayed payments. The use of instruments tailored to the needs of the counterparty organizes the relations between the parties. They are aware of the consequences of failure to perform the contract on time, the costs associated with it and, when using the indicated methods, usually try to prevent arrears.
Keywords: late payment; entrepreneurs; law; finance; management; risk; bankruptcy; restructuring